2019
DOI: 10.1177/0300060519831570
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass and systemic immune-inflammation indices with endocrine therapy resistance in luminal breast cancers

Abstract: Objective To explore correlations between body mass index (BMI), preoperative systemic immune-inflammation index (SII) and endocrine therapy resistance, and evaluate BMI and SII as predictors of resistance, in patients with luminal breast cancer. Methods This retrospective study included patients with luminal breast cancer who underwent endocrine therapy at Hebei General Hospital. Relationships between BMI and SII subgroups, and clinicopathological parameters were analysed using χ2-tests. Disease-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
(42 reference statements)
1
16
0
1
Order By: Relevance
“…The endpoint was OS in eight studies and PFS/DFS in six studies. Furthermore, the association of the SII index with LNM and LVI was also reported in five [11,13,14,21,22] and two [14,22] studies, respectively. All these studies were retrospectively performed in China (n = 6), Italy (n = 1), USA (n = 1), or Spain (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 66%
See 2 more Smart Citations
“…The endpoint was OS in eight studies and PFS/DFS in six studies. Furthermore, the association of the SII index with LNM and LVI was also reported in five [11,13,14,21,22] and two [14,22] studies, respectively. All these studies were retrospectively performed in China (n = 6), Italy (n = 1), USA (n = 1), or Spain (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 66%
“…No additional records were identified through manual searching. Finally, 9 published articles involving 2724 patients were included in this meta-analysis [11][12][13][14][15][16][20][21][22]. Among these 9 studies, two [11,14] contained the training and validation cohorts from different hospitals, and thus, 11 datasets were totally used for statistical analysis (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SII has been used to evaluate the pretreatment balance between inflammatory factors and immune status of patients with cancer [5][6][7][8]. The SII is associated with the prognosis of patients with breast cancer, although the results are controversial [9][10][11][12][13][14][15][16]. Therefore, we performed the current meta-analysis to identify the prognostic impact of the SII in patients with breast cancer by aggregating all available data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological and clinical studies have found that inflammatory responses are associated with breast tumors. 6,7 Inflammation constitutes part of the tumor microenvironment, and changes in inflammatory cells affect tumor progression, including breast cancer cell proliferation, invasion, decreased immunity, metastasis, and so on. 8,9 Tumor inflammatory response may be a potential target for treating tumors.…”
Section: Introductionmentioning
confidence: 99%